THE WAY PUSHKIN'S INNOVATIVE POETIC STRUCTURES AND THEMES RESONATE IN LERMONTOV'S NARRATIVE STYLE - Ruzibayeva Aziza Kahramanovna (The Conference Hub, 2025)
The paper covers the new forms of poetry and thematic issues in Alexander Pushkin's poetry and their echoes in Mikhail Lermontov's narrative technique. Lermontov, being a follower of Pushkin, takes up various poetic devices and thematic problems such as nature, romance, and existential crisis and creates an original narrative reflecting Pushkin's influence. By analyzing specific instances in the two authors, this study shows the dynamic interplay of structure and content, describing how Pushkin's legacy still affects the Russian literary sphere through Lermontov's prose.
Keywords: Pushkin, Lermontov, poetic structures, narrative style, Russian literature, romanticism, themes, literary influence.